Applications of carbon nanotubes and polymeric micro‐/nanoparticles in fish vaccine delivery: progress and future perspectives. (10th February 2021) - Giri, Sib Sankar; Kim, Sang Guen; Kang, Jeong Woo; Kim, Sang Wha; Kwon, Jun; Lee, Sung Bin; Jung, Won Joon; Park, Se Chang
Abstract: Newly evolving strains of pathogenic microorganisms in aquaculture are posing formidable challenge in controlling and/or eradication of diseases affecting aquaculture. Many research studies have aimed to address this challenge, and the delivery of vaccines using biocompatible nano‐delivery systems is widely investigated. Nanoparticles (NPs) have tremendous potential for application as delivery vehicles of novel vaccines. At present, various polymeric and non‐polymeric NPs are utilized to deliver vaccines in aquatic species. This review comprehensively discusses recent research advancements in the utilization of carbon nanotubes and polymeric micro‐/nanoparticles for the delivery of drug/nutrients to control fish diseases. Further, this review compares the potentials of various vaccine delivery systems utilized to control fish pathogens. The necessity of non‐toxic and eco‐friendly strategies for aquaculture has also been emphasized in this review.